2016
DOI: 10.3310/hsdr04110
|View full text |Cite
|
Sign up to set email alerts
|

Do-not-attempt-cardiopulmonary-resuscitation decisions: an evidence synthesis

Abstract: BackgroundCardiac arrest is the final common step in the dying process. In the right context, resuscitation can reverse the dying process, yet success rates are low. However, cardiopulmonary resuscitation (CPR) is a highly invasive medical treatment, which, if applied in the wrong setting, can deprive the patient of dignified death. Do-not-attempt-cardiopulmonary-resuscitation (DNACPR) decisions provide a mechanism to withhold CPR. Recent scientific and lay press reports suggest that the implementation of DNAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 126 publications
(630 reference statements)
0
47
0
1
Order By: Relevance
“…Receiving CPR when it is unlikely to be successful is a major concern expressed by patients approaching the end of their natural lives, and by their relatives 1 2. Moreover, prognostic information influences patient preference: fewer elderly patients wish to undergo CPR once a clinician has explained the probability of survival 3…”
Section: Introductionmentioning
confidence: 99%
“…Receiving CPR when it is unlikely to be successful is a major concern expressed by patients approaching the end of their natural lives, and by their relatives 1 2. Moreover, prognostic information influences patient preference: fewer elderly patients wish to undergo CPR once a clinician has explained the probability of survival 3…”
Section: Introductionmentioning
confidence: 99%
“…In other countries resuscitation would be provided in such circumstances (28). In some jurisdictions, advanced decisions to withhold resuscitation may be recorded prior to a cardiac arrest (29,30).…”
Section: Smart Technologies For Activation Of Lay Respondersmentioning
confidence: 99%
“…1 A key requirement of effective patientcentered health care is the involvement of the patient in decision making. It is therefore timely that Making decisions about CPR more patient centered is a worthy goal; for decades, these decisions were hidden or talked about in code, 3 and as Becker et al 2 reference, discussions are still often avoided or done badly. Part of clinicians' reluctance to discuss CPR with patients may stem from a widely acknowledged problem with the interpretation of DNR documentation.…”
mentioning
confidence: 99%
“…Part of clinicians' reluctance to discuss CPR with patients may stem from a widely acknowledged problem with the interpretation of DNR documentation. In a 2016 review of DNR decisions across the United Kingdom, 3 a key concern reported by clinicians was the perception that DNR decisions were being misinterpreted to mean do not provide any treatment. An accompanying systematic review of international studies 4 found that DNR decisions were associated with fewer invasive medical treatments, reduced escalation to medical and intensive care staff in the event of deterioration, fewer nursing observations, and less robust basic care, including less pain relief and altered fluid intake.…”
mentioning
confidence: 99%